O desenho infantil potencializado pelos estudos da cultura visual e pela educação estética (Olhar de Professor, 2022)
This article consists of a qualitative research based on pedagogical intervention during visual arts classes and presents reflections on drawing as an expressive language potentiated by actions mediated by the teacher, enriched by visual amplification from aesthetic education. The teaching practice started from a concern about the use of stereotypes and animism in children’s drawings from the 1st to the 5th grade of the elementary school classes. The analysis was carried out based on the concept of “drawings received” by Vianna (2012) with the pedagogical intervention based on the concept of “cultivated drawing” by Iavelberg (2013, 2017), on the “Visual Culture Studies” proposed by Hernández (2000, 2007) and through the “aesthetic education” based on Vigotski (2003). The experience demonstrated the presence of images received and the possibilities for their transformation and evidenced the need to deepen the inquiries raised that are under development in Master research.
Keywords: Children's drawing. Visual Culture. Aesthetic Education.